Human resource governance: what does governance mean for the health workforce in low- and middle-income countries? - Kaplan Avril D; Dominis Sarah; Palen John GH; Quain Estelle E (BMC, 2013)
Abstract Background Research on practical and effective governance of the health workforce is limited. This paper examines health system strengthening as it occurs in the intersection between the health workforce and governance by presenting a framework to examine health workforce issues related to eight governance principles: strategic vision, accountability, transparency, information, efficiency, equity/fairness, responsiveness and citizen voice and participation. Methods This study builds off of a literature review that informed the development of a framework that describes linkages and assigns indicators between governance and the health workforce. A qualitative analysis of Health System Assessment (HSA) data, a rapid indicator-based methodology that determines the key strengths and weaknesses of a health system using a set of internationally recognized indicators, was completed to determine how 20 low- and middle-income countries are operationalizing health governance to improve health workforce performance. Results/discussion The 20 countries assessed showed mixed progress in implementing the eight governance principles. Strengths highlighted include increasing the transparency of financial flows from sources to providers by implementing and institutionalizing the National Health Accounts methodology; increasing responsiveness to population health needs by training new cadres of health workers to address shortages and deliver care to remote and rural populations; having structures in place to register and provide licensure to medical professionals upon entry into the public sector; and implementing pilot programs that apply financial and non-financial incentives as a means to increase efficiency. Common weaknesses emerging in the HSAs include difficulties with developing, implementing and evaluating health workforce policies that outline a strategic vision for the health workforce; implementing continuous licensure and regulation systems to hold health workers accountable after they enter the workforce; and making use of health information systems to acquire data from providers and deliver it to policymakers. Conclusions The breadth of challenges facing the health workforce requires strengthening health governance as well as human resource systems in order to effect change in the health system. Further research into the effectiveness of specific interventions that enhance the link between the health workforce and governance are warranted to determine approaches to strengthening the health system.